The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1002/hon.955
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and clinical significance of 18F–2‐fluoro‐2‐deoxy‐D‐glucose (FDG) uptake in the thyroid gland on PET or PET‐CT in patients with lymphoma

Abstract: F(18) -2-fluoro-2-deoxy-D-glucose (FDG) positron emission tomography (PET) has become a well established tool in staging and assessing therapy response in lymphoma. Incidental thyroid uptake on PET is not uncommon and can pose a diagnostic and management challenge. We retrospectively evaluate the prevalence and clinical significance of incidental FDG uptake in the thyroid gland in patients with lymphoma. 1868 lymphoma patients underwent PET and PET-CT between August 2002 and August 2008. 52 patients (2.8%) dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…They also reported that the maximum SUV was significantly greater for malignant than benign lesions 84 . In our own experience of 1868 patients with lymphoma, abnormal focal FDG uptake within the thyroid was seen in 1.6% of patients, 30% of which was subsequently found to be malignant, comprising a mix of intercurrent thyroid carcinomas as well as lymphomatous involvement of the thyroid, and we observed no difference in SUV in benign compared with malignant causes of focal thyroid uptake 85 …”
Section: Clinical Applicationssupporting
confidence: 57%
“…They also reported that the maximum SUV was significantly greater for malignant than benign lesions 84 . In our own experience of 1868 patients with lymphoma, abnormal focal FDG uptake within the thyroid was seen in 1.6% of patients, 30% of which was subsequently found to be malignant, comprising a mix of intercurrent thyroid carcinomas as well as lymphomatous involvement of the thyroid, and we observed no difference in SUV in benign compared with malignant causes of focal thyroid uptake 85 …”
Section: Clinical Applicationssupporting
confidence: 57%
“…The purpose of this review is to enter into an initial exploratory phase in order to understand the real nature and impact of the problems related to lymphoma and thyroid. This is done through a careful examination of existing evidence regarding a range of issues that are central to the topic: thyroid diseases at risk of lymphoma development, primary thyroid lymphoma (PTL), and thyroid involvement in primitive nodal or extranodal lymphomas . Also, another learning objective is to understand the risk of thyroid dysfunction during therapy with new agents for lymphomas, how they will influence clinical practice, and the significance of incidental imaging–related findings …”
Section: Introductionmentioning
confidence: 99%
“…Incidental focal thyroid uptake carries an approximately 30% risk of malignancy [14,19] while 50-80% cases of focal colorectal FDG uptake are due to pre-malignant polyps or carcinoma [15]. A marked difference in metabolic activity between the known site of malignancy and the incidentally detected lesion, or a discordant metabolic response to therapy, are also scan features suggestive of a second pathology [9].…”
Section: Discussionmentioning
confidence: 97%
“…Although the FDG avidity of incidental malignant or pre-malignant lesions tended to have a higher SUV max (mean = 8.8 vs. 4.8) in our cohort, the number of patients for each specific organ location was too small for us to make general recommendation and warrants further studies with a larger number of patients. From our previous experience of incidental focal thyroid or colorectal lesions found on PET, there is no reliable cut-off or threshold based on metabolic activity where a malignant lesion is more likely [14,15,19].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation